2023
DOI: 10.1002/anie.202216586
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Trichlorides Enabling an Improved Chlorine Technology

Abstract: Chlorine plays a central role for the industrial production of numerous materials with global relevance. More recently, polychlorides have been evolved from an area of academic interest to a research topic with enormous industrial potential. In this minireview, the value of trichlorides for chlorine storage and chlorination reactions are outlined. Particularly, the inexpensive ionic liquid [NEt 3 Me][Cl 3 ] shows a similar and sometimes even advantageous reactivity compared to chlorine gas, while offering a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…of the electricity consumed in Germany is used for chlor-alkali electrolysis. 2 Thus, a "technical problem" like chlorine storage has serious implications for sustainability. TEMACl 3 is an ionic liquid, which minimizes the risk of uncontrolled release of toxic gases from leaks during transportation and storage (see Figure 1).…”
Section: Trichlorides and Multidimensional Socioeconomic Issuesmentioning
confidence: 99%
See 4 more Smart Citations
“…of the electricity consumed in Germany is used for chlor-alkali electrolysis. 2 Thus, a "technical problem" like chlorine storage has serious implications for sustainability. TEMACl 3 is an ionic liquid, which minimizes the risk of uncontrolled release of toxic gases from leaks during transportation and storage (see Figure 1).…”
Section: Trichlorides and Multidimensional Socioeconomic Issuesmentioning
confidence: 99%
“…Riedel and co-workers have recently established that alkylammonium trichlorides could be a promising solution. 2,13 In particular, the commercially available triethylmethylammonium chloride [NEt 3 Me]Cl was found to be a suitable chlorine storage material, which forms the demonstrated that the trichloride [NEt 3 Me][Cl 3 ] shows a similar reactivity as elemental chlorine. However, it is an ionic liquid with a low chlorine vapor pressure (0.9 bar at 20 °C) that is safe and easy to handle.…”
mentioning
confidence: 99%
See 3 more Smart Citations